Invitro: Evaluasi Aktifitas Peluruhan Batu Ginjal Ekstrak Daun Kemangi (Ocimum Basilicum) Menggunakan Spektrofotometer Serapan Atom: Invitro: Evaluation of Anticalculi Activity with Kemangi Leaf Extract (Ocimum Basilicum) Using Atomic Absorption Spectrophotometer - Meliza Harianja; Havizur Rahman; Sri Wigati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
A kidney stone is a disease that is quite often found in the community. Kidney stone disease is characterized by the formation of small stones due to precipitation in the urine. This stone can clog urethra and cause pain. The most common kidney stone content is calcium oxalate. Kemangi (Ocimum basilicum) contains several secondary metabolites such as flavonoids, saponins, phenols, and tannins. The content of secondary metabolites is thought to shed kidney stone. This study aims to reveal other properties of kemangi plant as anticalculi. Method: The stages in this study consisted of making kemangi leaf ethanol extract, extract characterization, phytochemical extract screening, kidney stone calcium making, and kidney stone calcium decay test stage. Testing the effect of the destruction of kidney stone is carried out in vitro by testing the rate of decay of kidney stone calcium components in various concentrations of ethanol extracts of kemangi leaf in physiological NaCl. Kidney stone calcium decay was analyzed by atomic absorption spectrophotometer (ASS). Data were analyzed with one-way ANOVA and continued with the LSD test. Results: ethanol extract of kemangi leaf at a concentration of 600 ? x ?1600 ppm could shed kidney stone calcium significantly greater than negative controls. Conclusion: the kemangi leaf ethanol extract has potential as the destruction of kidney stone.